The Impact of Digital Platform Use in Serbia on the Dynamics of the Private-Public Relationship - Nešić, Dejana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The study explores the transformation of the public sphere in digital environments, focusing on how users engage with digital platforms along a private-public continuum. The main objective is to examine the purposes for which the individuals use digital platforms and the implications of these practices for contemporary forms of public engagement and public discourse. The significance of the topic lies in the fact that digital platforms redefine the modes of communication, participation, and visibility, directly influencing socio-cultural and political patterns. Understanding whether the purposes of platform use are predominantly private or public provides insight into how these practices shape and transform the contemporary public sphere with implications for media policy, education, and social discourse. These questions are highly relevant for a digitally connected society, which in theory is known as the network society (Castells, 2000; 2004).Data were collected through an online survey administrated to 762 participants via Facebook and email. The analysis, based on percentages and percentage rankings, provides insights into the purposes rather than the perceptions of digital platform use. Findings indicate that while social networks are an integral part of daily life, they are not primarily used for collective or public engagement. Websites remain the most frequently used platforms, mostly for browsing, information seeking, reading, learning, and personal communication. These activities, although potentially fostering informed and monitorial citizenship (Jenkins, 2006), are largely individual and private in character.Among social networks, Facebook functions as a hybrid private-public network, Instagram serves mainly as private, but partly informational purposes, while X stands out as a platform of information and debate, operating as a form of public sphere. Nevertheless, overall participation in public debates or initiatives remains marginal. Chi-square analyses confirmed a significant link between platform type and primary communication function, highlighting Facebook and Instagram’s hybrid character and X’s public orientation with usage patterns consistent across age and education groups. The results confirm that communication and messaging represent the main motivations for platform use, while public or political engagements is limited.Overall, the findings support the core research hypothesis that private purpose dominate over public ones. Although certain practices show potential for digital citizenship, dominant usage patterns contribute more to maintaining personal relations and leisure than to democratic processes. Since the sample consisted of online users recruited through Facebook and email, the results should be interpreted with caution due to limited generalizability.
Keywords: internet websites; digital platforms; network society; platform society; mass self-communication; interpersonal communication; public/private purposes